Enhanced photoluminescence property and mechanism of Eu3+‐doped tellurite glasses by the silver and gold nanoparticles. Issue 2 (20th September 2017) - Yu, Chengye; Yang, Zhengwen; Qiu, Jianbei; Song, Zhiguo; Dacheng, Zhou
Abstract: In this work, the silver or gold nanoparticle single‐existing and co‐existing tellurite glasses doped with Eu 3+ were prepared, and the influence of gold or silver nanoparticles on the photoluminescence of tellurite glasses doped with Eu 3+ were investigated. The photoluminescence of tellurite glasses doped with Eu 3+ was enhanced by the surface plasmon absorption of gold or silver nanoparticles, and the maximum luminescence enhancement factors caused by the silver and gold nanoparticles are 4.8 and 3.5 factors, respectively. The differentiation of luminescence enhancement mechanisms caused by the gold or silver nanoparticles was demonstrated. The enhanced luminescence mechanism of the Au nanoparticle single‐existing tellurite glasses doped with Eu 3+ was from the increasing of radiative decays rate caused by the Au nanoparticles. The excitation field enhancement caused by the Ag nanoparticles was responsible for the luminescence enhancement of the Ag single‐existing tellurite glasses doped with Eu 3+ . About 4.2‐factor luminescence enhancement was observed in the Ag and Au nanoparticle co‐existing tellurite glasses doped with Eu 3+, which is attributed to the increasing of radiative decays rate and excitation field enhancement caused by the Au and Ag nanoparticles.